1998
DOI: 10.1046/j.1365-2141.1998.01121.x
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombotic changes in children with sickle cell disease: relationships to cerebrovascular disease and transfusion

Abstract: Summary. Vascular occlusion has a central role in the pathophysiology of sickle cell disease (SCD) and, although there is little evidence that thrombosis alone is responsible, patients with sickle cell disease are known to have an illdefined but increased thrombotic risk. The most serious complication of this in childhood is stroke which occurs in 7-10% of children and a further 14% have asymptomatic cerebrovascular disease (CVD) on imaging. We have performed a comprehensive profile of coagulation inhibitors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 62 publications
0
45
1
1
Order By: Relevance
“…Low levels of protein C and S have been associated with ischemic stroke, 711 and other markers of hypercoagulability have been reported in sickle cell disease patients, albeit not directly linked to stroke. 712,713 Cerebral venous sinus thrombosis (CVST) is another mechanism of brain ischemia reported in sickle cell disease patients. 714 Cardiogenic embolism appears either rare or underreported.…”
Section: Sickle Cell Diseasementioning
confidence: 99%
“…Low levels of protein C and S have been associated with ischemic stroke, 711 and other markers of hypercoagulability have been reported in sickle cell disease patients, albeit not directly linked to stroke. 712,713 Cerebral venous sinus thrombosis (CVST) is another mechanism of brain ischemia reported in sickle cell disease patients. 714 Cardiogenic embolism appears either rare or underreported.…”
Section: Sickle Cell Diseasementioning
confidence: 99%
“…In fact, it was shown that in a group of chronically transfused children, certain coagulation parameters had normalized after transfusion, with a reduction (although not a normalization) in TAT levels in the small patient cohort evaluated. 7 From the analyses presented here and the previous preliminary observation of Styles et al, 29 we suggest that the level of erythrocyte PS during such a transfusion regimen may be of relevance in the monitoring of large vessel remodeling in SCD. In addition, because previous evidence points to a role for erythrocyte PS in red cell endothelial adhesion, 25 and because adhesion is a significant factor in the propensity to microvascular occlusion, the importance of this biologic marker as a potential indicator of macrovascular and microvessel pertubations in SCD should be further assessed.…”
Section: Discussionmentioning
confidence: 86%
“…One of the complications of SCD is a thrombophilic state associated with complex pertubations of plasma and cellular hemostatic mechanisms. 1,2 These changes include evidence for thrombin generation, [3][4][5][6][7][8] depletion of natural anticoagulants, 6-10 the activation of cellular elements including white cells [11][12][13] and platelets, 2,14 and increased levels of circulating soluble tissue factor and microvascular endothelial cells with a tissue factor phenotype. [15][16][17] Numerous investigations have been conducted to elucidate the mechanisms responsible for the prothrombotic state.…”
Section: Introductionmentioning
confidence: 99%
“…42 It has been proposed that the beneficial effect may in part be related to normalization of the levels of F1.2, 18 although another study found no significant reduction in thrombin generation when children with SCD undergoing chronic transfusion were compared with control patients. 43 Treatment with both hydroxyurea and decitabine also decrease plasma markers of thrombin generation. 44,45 Antiplatelet agents There are only a few reports on the use of antiplatelet agents in SCD 35,[46][47][48][49] (Table 1).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%